Internal quality process management evaluation in higher education by students - Lucie Vnoučková; Hana Urbancová; Helena Smolová (DANUBE: Law, Economics and Social Issues Review, 2018)
With the increasing importance of higher education, there is also growing public concern about its productivity. Therefore, the aim of the study is to evaluate the key internal quality management processes by student evaluation and to reveal the key factors of an effective internal quality process management. The indicators used are based on student satisfaction with the education process. The results are based on a quantitative survey using questionnaire data collection within a sample of students, and qualitative research within target groups. Descriptive statistics and two dimensional statistical methods were used to evaluate the quantitative results. The results show student evaluation of five key areas of the internal quality process management evaluation: leadership and strategic planning, student and stakeholder focus, measurement of student learning outcomes, human resource planning and educational process management. A limitation of the study is its narrow focus on a case study of a single private university.
Keywords: 330; Internal Quality; Assessment; Process; Management; Education; University